2011
DOI: 10.1038/bjc.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

ASPM and microcephalin expression in epithelial ovarian cancer correlates with tumour grade and survival

Abstract: Background:The clinico-pathological and molecular heterogeneity of epithelial ovarian cancer (EOC) complicates its early diagnosis and successful treatment. Highly aneuploid tumours and the presence of ascitic fluids are hallmarks of EOC. Two microcephaly-associated proteins, abnormal spindle-like microcephaly-associated protein (ASPM) and microcephalin, are involved in mitosis and DNA damage repair. Their expression is deregulated at the RNA level in EOC. Here, ASPM and microcephalin protein expression in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 29 publications
(37 reference statements)
7
58
0
Order By: Relevance
“…Our recent EOC study determined a correlation between Microcephalin and ASPM levels with tumour grade and survival in cell lines and in primary cultures of malignant cells derived from ovarian ascites samples [36]. In this work we have validated our original findings in a larger scale study utilising EOC tissue samples and have investigated the roles of Microcephalin and ASPM in EOC progression.…”
Section: Introductionsupporting
confidence: 55%
“…Our recent EOC study determined a correlation between Microcephalin and ASPM levels with tumour grade and survival in cell lines and in primary cultures of malignant cells derived from ovarian ascites samples [36]. In this work we have validated our original findings in a larger scale study utilising EOC tissue samples and have investigated the roles of Microcephalin and ASPM in EOC progression.…”
Section: Introductionsupporting
confidence: 55%
“…The reports in recent years showed that MCPH1 expression was related to several female cancers, such as breast cancer and ovarian cancer (Brüning-Richardson et al, 2011). Compared with normal tissues, MCPH1 expression showed much lower in breast cancer and ovarian cancer, these findings indicated that MCPH1 plays a role in the progression of cancerization.…”
Section: Discussionmentioning
confidence: 68%
“…In normal breast epithelial cells, MCPH1 was expressed as protein only in nucleus, but in breast cancer cells, It's expression was not only observed in nucleus but also in cytoplasm, The similar situation had been found in our study, the bronchial epithelial cells showed strong nuclear expression of MCPH1 protein, but MCPH1 was mainly expressed in the cytoplasm of lung cancer cells, the nuclear localization meaned that MCPH1 was consiten with the role in DNA repair and cell cycle regulation (Jo et al, 2013). The further research is needed to explain the cytoplasmic MCPH1 expression, preliminary researchs have shown that MCPH1 expression in cytoplasm is likely to be correlative with the progression and aggressiveness of breast cancer (Jo et al, 2013) and ovarian cancer (Brüning-Richardson et al, 2011). Those findings indicate that the MCPH1 played multiple roles in maintaining genomic instability, and cancer development, MCPH1 may function as a novel tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 97%
“…Human primary cancer cells are highly heterogeneous, in contrast to cell culture systems. [74][75][76] Indeed, genetic heterogeneity of malignant cells is one of the key factors in the development of chemoresistance. 70 Lastly, flavopiridol treatment caused a significant reduction in AKT-Ser473 phosphorylation in human U87MG glioblastoma (Figs.…”
Section: Methodsmentioning
confidence: 99%